2018
DOI: 10.4149/gpb_2018028
|View full text |Cite
|
Sign up to set email alerts
|

Morin inhibits PDGF-induced proliferation, migration, and invasion of vascular smooth muscle cells via modulating p27KIP1, AKT, and MMP-9 activities

Abstract: Hyper-proliferation and migration of vascular smooth muscle cells (VSMCs) are closely associated with atherosclerosis. Recently, the flavonol morin has been reported to exhibit potent anti-oxidant and anti-inflammatory activities. Therefore, we investigated molecular mechanisms of morin in VSMCs stimulated by PDGF. Morin effectively inhibited PDGF-stimulated proliferation of VSMCs through a G1 cell-cycle arrest, leading to down-regulation of CDK2, CDK4, cyclin D1, and cyclin E proteins. Interestingly, PDGF mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, Molecular simulation demonstrated the direct binding of luteolin to TGFBR1 (81). A similar effect has been reported for several flavonoids including quercetin (82), morin (83), cardamonin (84), xanthohumol (85), baicalin (86), kaempferol (87), apigenin (88), and genistein (89), etc. Various mechanisms underpin this activity including reduced activation of mitogen-activated protein kinase (82), modulation of p27KIP1, Akt, and MMP-9 functions (83), down-regulation of p38 MAPK, Akt, and extracellular regulated protein kinase phosphorylation (84), activation of maternally expressed gene 3/p53 signaling pathway (86), modulation of microRNA expression (87), and/or suppression of oxidative stress (90).…”
Section: Flavonoids Improve Vascular Smooth Muscle Cell Functionsupporting
confidence: 70%
“…Furthermore, Molecular simulation demonstrated the direct binding of luteolin to TGFBR1 (81). A similar effect has been reported for several flavonoids including quercetin (82), morin (83), cardamonin (84), xanthohumol (85), baicalin (86), kaempferol (87), apigenin (88), and genistein (89), etc. Various mechanisms underpin this activity including reduced activation of mitogen-activated protein kinase (82), modulation of p27KIP1, Akt, and MMP-9 functions (83), down-regulation of p38 MAPK, Akt, and extracellular regulated protein kinase phosphorylation (84), activation of maternally expressed gene 3/p53 signaling pathway (86), modulation of microRNA expression (87), and/or suppression of oxidative stress (90).…”
Section: Flavonoids Improve Vascular Smooth Muscle Cell Functionsupporting
confidence: 70%
“…Studies have shown that MMP-9 expression and cellular migration are mediated by activation of the PI3K/Akt signaling pathways, playing key roles in ECM degradation and VSMC invasion and migration. Mulberry pigment can effectively inhibit the activity of PDGFinduced MMP-9 by downregulating the binding activity of NF-κB, thus reducing the migration and invasion of SMCs (Shin et al, 2018). Naringin (Figure 3) at concentrations of 10-25 μM blocked the TNF-α-induced PI3K/AKT/mTOR/p70S6K pathway in VSMCs at concentrations of 10-25 μM, and the expression of MMP-9 was inhibited by the transcription factors NF-κB and AP-1 (Lee et al, 2009).…”
Section: Pi3k and Smcsmentioning
confidence: 99%
“…In the present study, the results of the transwell migration assay showed that the migration ability of MDA‐MB‐231 breast cancer cells was inhibited, and the expression of MMP9 was decreased in response to an RCCS‐simulated microgravity environment. As a protease with broad biological functions, MMP9 plays a key role in tumor invasion, metastasis, angiogenesis, and biosensing . Based on the results of the present study, it was concluded that the decrease of MMP9 expression in MDA‐MB‐231 breast cancer cells in a simulated microgravity environment might be closely related to a decrease in migration ability.…”
Section: Discussionmentioning
confidence: 52%